Emergency appendicectomy in Australia: findings from a multicentre, prospective study. Issue 9 (7th July 2017) - Arthur, Thomas; Gartrell, Richard; Manoharan, Bavahuna; Parker, David; ,
Abstract: Background: Emergency appendicectomy is the most common emergency surgical procedure performed in Australia. Despite this frequency, there is a relative paucity of contemporary, broad‐based, local data that examine how emergency appendicectomies are currently performed and what are the outcomes from these operations. Methods: A multicentre, prospective, observational study was performed. Patients were recruited by local investigators for a period of 2 months with 30‐day follow‐up. Patients were eligible for study inclusion if they underwent an emergency appendicectomy for suspected acute appendicitis. The primary outcome of the study was the negative appendicectomy rate (NAR), with secondary outcomes including 30‐day complication rates, method of operation and conversion rates. Results: A total of 1189 patients were recruited across 27 centres. The NAR across all centres was 19.0%. 98.2% of appendicectomies were performed with a laparoscopic‐first approach. The rate of conversion from laparoscopy to open operation was 2.4%. 9.4% of patients were recorded as having one or more of the following complications: readmission (6.6%), surgical site infection (1.9%), intra‐abdominal abscess (2.7%) or further intervention (1.5%). Patients who had an open operation had higher rates of readmission and surgical site infection. Conclusion: The NAR found in this study is within the traditional measures of acceptance; however, this rate is high when measured against modern international benchmarks.